Prepregs and molded products
A halogen-free prepreg composition using urethane (meth)acrylate, ethylenically unsaturated monomer, and phosphorus-based flame retardants addresses environmental concerns and maintains flame retardancy, achieving fast curing and high mechanical strength in molded articles.
Patent Information
- Application Number
- JP2024560299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-05-30
- Filing Date
- 2024-05-16
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-05-16
AI Technical Summary
Existing prepregs containing halogen-containing compounds for flame retardancy pose environmental concerns and need to be replaced with halogen-free alternatives that maintain excellent flame retardancy.
A prepreg composition comprising urethane (meth)acrylate, an ethylenically unsaturated monomer, a polymerization initiator, reinforcing fibers, and a halogen-free phosphorus-based flame retardant, which includes a polyisocyanate with an aromatic skeleton and a reaction product of polyisocyanate and polyol, achieves flame retardancy without halogens.
The prepreg composition provides excellent flame retardancy in molded articles, meeting UL standards, while avoiding environmental impacts from halogen release, with fast curing properties and improved mechanical properties.
Smart Images

Figure 0007605388000001 
Figure 0007605388000002 
Figure 0007605388000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a prepreg and a molded article thereof. [Background technology]
[0002] Fiber-reinforced resin composite materials reinforced with reinforcing fibers such as carbon fibers and glass fibers have attracted attention for their characteristics of being lightweight yet excellent in heat resistance and mechanical strength, and are being increasingly used in various structural applications, including the housings and various components of automobiles and aircraft. As a molding method for these fiber-reinforced resin composite materials, for example, a method is used in which an intermediate material called a prepreg, in which reinforcing fibers are impregnated with a thermosetting resin, is used, and the material is cured and molded by autoclave molding or press molding.
[0003] Prepregs are required to be flame retardant depending on the application. For example, in the case of applications such as construction applications and battery cases for automobiles. In particular, lithium ion secondary batteries, which are often used as batteries for electric vehicles, contain organic solvents and are therefore likely to catch fire. Prepregs for molding battery cases for housing the lithium ion secondary batteries are required to meet the flame retardant standards designated by UL (Underwriters Laboratories, Inc.) to ensure safety in use.
[0004] Conventionally, as a prepreg having flame retardancy, a prepreg containing a halogen-containing compound such as brominated phenol as a flame retardant has been known (for example, see Patent Document 1). However, the halogen-containing compound has the disadvantage of being a concern for its impact on the environment. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2009-521666 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a prepreg that can achieve excellent flame retardancy without containing a halogen-containing compound, and a molded article thereof. [Means for solving the problem]
[0007] The present inventors have found that a prepreg containing a specific urethane (meth)acrylate, a specific ethylenically unsaturated monomer, a polymerization initiator, reinforcing fibers and a specific flame retardant can solve the above problems, and have completed the present invention.
[0008] That is, the present invention relates to a prepreg comprising a urethane (meth)acrylate (A), an ethylenically unsaturated monomer (B) other than the urethane (meth)acrylate (A), a polymerization initiator (C), reinforcing fibers (D), and a flame retardant (E), wherein the urethane (meth)acrylate (A) is a reaction product of a polyisocyanate (a1) and a polyol (a2) having an ethylenically unsaturated group and an aromatic skeleton, and / or a reaction product of the polyisocyanate (a1), a polyol (a3) having no ethylenically unsaturated group and an aromatic skeleton, and a hydroxyalkyl (meth)acrylate (a4), and the flame retardant (E) contains one or more halogen-free phosphorus compounds. Effect of the Invention
[0009] The prepreg of the present invention can achieve excellent flame retardancy in a molded article obtained from the prepreg, even though it does not contain a halogen-containing compound. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The prepreg of the present invention contains a urethane (meth)acrylate (A), an ethylenically unsaturated monomer (B) other than the urethane (meth)acrylate (A), a polymerization initiator (C), reinforcing fibers (D), and a flame retardant (E), wherein the urethane (meth)acrylate (A) is a reaction product of a polyisocyanate (a1) and a polyol (a2) having an ethylenically unsaturated group and an aromatic skeleton, and / or a reaction product of the polyisocyanate (a1), a polyol (a3) having no ethylenically unsaturated group and an aromatic skeleton, and a hydroxyalkyl (meth)acrylate (a4), and the flame retardant (E) contains one or more halogen-free phosphorus compounds.
[0011] The polyisocyanate (a1) preferably contains a polyisocyanate having a cyclic skeleton, since this further improves the heat resistance of the molded article. These polyisocyanates (a1) may be used alone or in combination of two or more kinds.
[0012] Examples of the polyisocyanate (a1) include 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, carbodiimide modified products of 4,4'-diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, nurate modified products, biuret modified products, and urethane imine modified products of diphenylmethane diisocyanate, polyol modified products modified with polyols having a number average molecular weight of 1,000 or less, such as diethylene glycol and dipropylene glycol, tolylene diisocyanate (TDI), tolidin diisocyanate, and the like. Examples of the polyisocyanates include aromatic polyisocyanates such as isocyanate, xylylene diisocyanate, 1,5-naphthalene diisocyanate, and tetramethyl xylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate (IPDI), hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, and norbornene diisocyanate; and aliphatic polyisocyanates such as hexamethylene diisocyanate, nurate-modified hexamethylene diisocyanate, biuret-modified hexamethylene diisocyanate, adduct, and dimer acid diisocyanate. Among these, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, carbodiimide-modified 4,4'-diphenylmethane diisocyanate, and polymethylene polyphenyl polyisocyanate are preferred because they further improve the heat resistance of the molded product. These polyisocyanates (a1) can be used alone or in combination of two or more kinds.
[0013] The polyol (a2) has an ethylenically unsaturated group and an aromatic skeleton. A multifunctional epoxy (meth)acrylate is preferred because it has improved heat resistance. For example, a reaction between a novolac epoxy resin such as a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, a bisphenol fluorene type epoxy resin, or a biscresol fluorene type epoxy resin, a phenol novolac type epoxy resin, or a cresol novolac type epoxy resin and (meth)acrylic acid is performed. It is preferably obtained by reacting an epoxy resin having an epoxy equivalent in the range of 180 to 500 with (meth)acrylic acid. The number of functional groups is preferably 1.5 to 3.0 in terms of the balance between heat resistance and strength properties.
[0014] The polyol (a3) does not have an ethylenically unsaturated group and has an aromatic skeleton. For example, alkylene oxide adducts of bisphenol compounds such as alkylene oxide adducts of bisphenol A, alkylene oxide adducts of bisphenol S, and alkylene oxide adducts of bisphenol F; alkylene oxide adducts of dihydroxybenzene compounds such as 1,3-bis(2-hydroxyethoxy)benzene and 1,4-bis(2-hydroxyethoxy)benzene; alkylene oxide adducts of biphenol compounds such as 2'-[(1,1'-biphenyl-4,4'-diyl)bisoxy]bisethanol; alkylene oxide adducts of dihydroxynaphthalene compounds, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, etc. Among these, alkylene oxide adducts of bisphenol compounds are preferred from the viewpoint of compatibility, heat resistance, water resistance, and balance of strength properties. More preferred are ethylene oxide adducts of bisphenol compounds, the average number of moles of which is 2 to 10 moles.
[0015] Examples of the hydroxyalkyl (meth)acrylate (a4) include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxy-n-butyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-n-butyl (meth)acrylate, and 3-hydroxy-n-butyl (meth)acrylate. Among these, 2-hydroxyethyl (meth)acrylate is preferred from the viewpoint of balance of strength properties. These hydroxyalkyl (meth)acrylates (a4) can be used alone or in combination of two or more kinds.
[0016] If necessary, polyols other than the polyols (a2) to (a4) can be used in combination as raw materials for the urethane (meth)acrylate (A). Examples of the other polyols that can be used include polyester polyols, acrylic polyols, polyether polyols, polycarbonate polyols, and polyalkylene polyols.
[0017] The molar ratio (a3 / a4) of the polyol (a3) to the hydroxyalkyl (meth)acrylate (a4) is preferably from 60 / 40 to 20 / 80, and more preferably from 50 / 50 to 30 / 70, in order to further improve heat resistance and curability.
[0018] The molar ratio (NCO / OH) of the isocyanate group (NCO) of the isocyanate compound to the hydroxyl group (OH) of the compound having a hydroxyl group, which are raw materials for the urethane (meth)acrylate (A), is preferably 0.7 to 1.3, more preferably 0.8 to 1.1, and even more preferably 0.8 to 1.0, in view of the balance between heat resistance and strength properties.
[0019] Examples of the ethylenically unsaturated monomer (B) include dimethacrylate of an ethylene oxide adduct of bisphenol A, tricyclodecane dimethanol dimethacrylate, 1,12 dodecane diol dimethacrylate, hydrogenated bisphenol A dimethacrylate, polytetramethylene glycol dimethacrylate, 9,9-bis[4-(2-methacryloyloxyethoxy)phenyl]fluorene, dimethacrylate of an ethylene oxide adduct of isosorbide, dimethacrylate of an ethylene oxide adduct of hydrogenated bisphenol A, trimethacrylate of an ethylene oxide adduct of trimethylolpropane, tetramethacrylate of an ethylene oxide adduct of pentaerythritol, and hexamethacrylate of an ethylene oxide adduct of dipentaerythritol. From the viewpoint of the balance of curability, heat resistance, and strength properties, the molecular weight is preferably 320 to 2,000, and the (meth)acrylic group equivalent is preferably 150 to 1,000, and more preferably 150 to 500. Similarly, in view of the balance between curability, heat resistance, and strength properties, the number of functional groups is preferably 2 to 4, and more preferably 2.
[0020] The content of the ethylenically unsaturated monomer (B) in the total of the urethane (meth)acrylate (A) and the ethylenically unsaturated monomer (B) (hereinafter abbreviated as "content (B)") is preferably 5 to 50 mass%, and more preferably 10 to 40 mass%, in order to further improve the balance between prevention of contamination of the working environment, handleability of the prepreg, and quality and productivity of the molded product.
[0021] The polymerization initiator (C) is not particularly limited, but is preferably an organic peroxide, such as a diacyl peroxide compound, a peroxy ester compound, a hydroperoxide compound, a ketone peroxide compound, an alkyl perester compound, a percarbonate compound, a peroxy ketal, etc., which can be appropriately selected according to the molding conditions. These polymerization initiators (C) can be used alone or in combination of two or more kinds.
[0022] Among these, it is preferable to use a polymerization initiator having a temperature of 60° C. or higher and 110° C. or lower to obtain a 10-hour half-life for the purpose of shortening the molding time. A polymerization initiator having a temperature of 70° C. or higher and 105° C. or lower is preferable because the prepreg has a long life at room temperature and can be cured in a short time (within 5 minutes) by heating, and by using it in the prepreg of the present invention, the curability and moldability are superior. Examples of such polymerization initiators include 1,6-bis(t-butylperoxycarbonyloxy)hexane, 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-amylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, t-butylperoxydiethyl acetate, t-butylperoxyisopropyl carbonate, t-butylperoxy2-ethylhexyl carbonate, t-amylperoxyisopropyl carbonate, t-amylperoxy2-ethylhexyl carbonate, t-hexylperoxyisopropyl carbonate, di-tert-butylperoxyhexahydroterephthalate, t-amylperoxytrimethylhexanoate, t-amylperoxyisononaate, t-hexylperoxy-2-ethylhexanoate, and n-butyl 4,4-di(t-butylperoxy)valerate. The most suitable organic peroxide is selected and used depending on the molding conditions.
[0023] The amount of the polymerization initiator (C) added is preferably within a range of 0.5 to 3 parts by mass per 100 parts by mass of the total of the urethane (meth)acrylate (A) and the ethylenically unsaturated monomer (B), since both the curing characteristics and storage stability are excellent.
[0024] Examples of the reinforcing fiber (D) include carbon fiber, glass fiber, silicon carbide fiber, alumina fiber, boron fiber, metal fiber, and organic fibers such as aramid fiber, vinylon fiber, and tetron fiber, among which carbon fiber or glass fiber is preferred, and carbon fiber is more preferred, since a molded product having higher strength and higher elasticity can be obtained. These reinforcing fibers (D) can be used alone or in combination of two or more kinds.
[0025] As the carbon fiber, various types of fibers such as polyacrylonitrile, pitch, and rayon can be used. Among these, polyacrylonitrile-based fibers are preferred because they can easily produce high-strength carbon fibers.
[0026] The shape of the reinforcing fiber (D) is not particularly limited, and examples thereof include reinforcing fiber tows in which reinforcing fiber filaments are bundled, unidirectional materials in which reinforcing fiber tows are aligned in one direction, woven fabrics or short cut reinforcing fibers, and nonwoven fabrics or papers made of short cut reinforcing fibers. However, it is preferable to use unidirectional materials as reinforcing fibers and laminate and mold them, since high mechanical properties can be obtained.
[0027] When short cut reinforcing fibers are used, it is preferable to use carbon fibers cut to 2.5 to 50 mm, as this improves the flowability in the mold during molding and the appearance of the molded product.
[0028] In the case of woven fabrics, examples include plain weave, twill weave, satin weave, and non-crimped fabrics, which are sheets in which fiber bundles are aligned in one direction or sheets layered at different angles and stitched to prevent them from unraveling.
[0029] Reinforced fiber count (fiber 1m 2 There is no particular restriction on the weight per unit, but it is recommended to use 10g / m 2 ~650g / m 2 The weight is preferably 10 g / m 2 If the fiber weight is more than 650g / m, the unevenness of the fiber width is small and the mechanical properties are good, which is preferable. 2 If the weight is less than 50, the resin is impregnated well, which is preferable. The weight is further preferably 50 to 500 g / m 2 More preferably, 50 to 300 g / m 2 is particularly preferred.
[0030] The content of the reinforcing fibers (D) in the prepreg of the present invention is preferably in the range of 20 to 85% by mass, more preferably in the range of 40 to 80% by mass, since this further improves the mechanical strength of the resulting molded article.
[0031] The flame retardant (E) contains one or more halogen-free phosphorus compounds. The halogen-free phosphorus compounds are compounds that contain phosphorus but do not contain halogen. The prepreg of the present invention contains the flame retardant (E), so that the molded article obtained from the prepreg can have excellent flame retardancy. In addition, since the flame retardant (E) is halogen-free (halogen-free), the impact on the environment due to the release of halogens during the manufacturing process of the prepreg or molded article can be prevented. Here, when a compound that does not contain halogen and does not contain phosphorus is used as the flame retardant, the molded article cannot have excellent flame retardancy.
[0032] Examples of the halogen-free phosphorus compound include red phosphorus, phosphonic acid esters, ammonium polyphosphate salts, phosphoric acid esters, aromatic phosphoric acid esters, aromatic condensed phosphoric acid esters, phosphazenes, etc. Examples of commercially available products include Nova Excel 140, Nonnen 73, FCP-770, DAIGUARD-880, TPP, TCP, CDP, PX-110, CR-733S, CR-741, PX-200, DAIGUARD-580, DAIGUARD-850, Rabitol FP-110, Rabitol FP-100, etc.
[0033] Incidentally, when the prepreg is heated, the radicals generated by the decomposition of the polymerization initiator (C) are added to the ethylenically unsaturated monomer (B), and the polymerization reaction proceeds. The polymerization heat generated by the polymerization reaction can shorten the time until the prepreg reaches the desired peak temperature during heating, and the prepreg can obtain fast curing properties. However, in the case of halogen-free phosphorus compounds that contain active hydrogen, the active hydrogen deactivates the radicals and hinders the progress of the polymerization reaction, and as a result, the time until the prepreg reaches the desired peak temperature during heating is delayed, or the peak temperature may not be reached. Therefore, it is preferable to use a halogen-free phosphorus compound that does not contain active hydrogen.
[0034] On the other hand, even if the halogen-free phosphorus compound contains active hydrogen, if it is a salt compound, the solubility of the salt in the resin component in the prepreg is low, so that the active hydrogen is less likely to deactivate the radicals, and therefore the hindrance of the polymerization reaction caused by the active hydrogen can be suppressed. As a result, it is possible to prevent the time until the desired peak temperature is reached in the prepreg during heating from being delayed or from not being able to reach the peak temperature, and the prepreg can obtain fast curing properties. That is, it is preferable to use a salt compound as the halogen-free phosphorus compound. The salt compound may or may not contain active hydrogen. And, in consideration of flame retardancy, availability, price, etc., ammonium phosphate is more preferable as the halogen-free salt compound.
[0035] That is, the halogen-free phosphorus compound is preferably a phosphorus compound not containing active hydrogen or an ammonium phosphate. The ammonium phosphate may contain active hydrogen or may not contain active hydrogen. However, in this specification, the phosphorus compound not containing active hydrogen does not include an ammonium phosphate not containing active hydrogen.
[0036] Examples of the phosphorus compound not containing active hydrogen include ammonium polyphosphate, phosphoric acid, phosphates, polyphosphoric acid, polyphosphates, etc. Examples of commercially available products include FCP-770, FCP-790, phosphoric acid, sodium phosphate, polyphosphoric acid, sodium polyphosphate, etc.
[0037] Commercially available products of the ammonium phosphate include FCP-770 and FCP-790.
[0038] Components other than those described above may be used as components of the prepreg of the present invention. For example, the prepreg may contain a thermosetting resin, a thermoplastic resin, a polymerization inhibitor, a curing accelerator, a filler, a low shrinkage agent, a release agent, a thickener, a viscosity reducer, a pigment, an antioxidant, a plasticizer, an antibacterial agent, an ultraviolet stabilizer, a reinforcing material, a photocuring agent, etc.
[0039] Examples of the thermosetting resin include vinyl ester resin, unsaturated polyester resin, phenol resin, melamine resin, furan resin, bismaleimide resin, etc. These thermosetting resins can be used alone or in combination of two or more kinds.
[0040] Examples of the thermoplastic resin include polyamide resin, polyethylene terephthalate resin, polybutylene terephthalate resin, polycarbonate resin, polyurethane resin, polypropylene resin, polyethylene resin, polystyrene resin, acrylic resin, polybutadiene resin, polyisoprene resin, and those modified by copolymerization. Among these, polyamide resin and polyurethane resin are preferred because they have a high effect of improving brittleness. These thermoplastic resins can be used alone or in combination of two or more. Thermoplastic resins can be added in particulate form or melted and mixed. When particulate thermoplastic resins are used, the particle size is preferably 30 μm or less, more preferably 5 to 20 μm, from the viewpoint of dispersibility in fibers.
[0041] Examples of the polymerization inhibitor include hydroquinone, trimethylhydroquinone, pt-butylcatechol, t-butylhydroquinone, toluhydroquinone, p-benzoquinone, naphthoquinone, hydroquinone monomethyl ether, phenothiazine, copper naphthenate, copper chloride, etc. These polymerization inhibitors can be used alone or in combination of two or more kinds.
[0042] Examples of the curing accelerator include metal soaps such as cobalt naphthenate, cobalt octenate, vanadyl octenate, copper naphthenate, and barium naphthenate, and metal chelate compounds such as vanadyl acetylacetate, cobalt acetylacetate, and iron acetylacetonate. Examples of amines include N,N-dimethylamino-p-benzaldehyde, N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-p-toluidine, N-ethyl-m-toluidine, triethanolamine, m-toluidine, diethylenetriamine, pyridine, phenylmorpholine, piperidine, and diethanolaniline. These curing accelerators can be used alone or in combination of two or more.
[0043] The fillers include inorganic compounds and organic compounds, and can be used to adjust the physical properties of the molded product, such as strength, elastic modulus, impact strength, and fatigue durability.
[0044] Examples of the inorganic compound include calcium carbonate, magnesium carbonate, barium sulfate, mica, talc, kaolin, clay, celite, asbestos, barite, baryta, silica, silica sand, dolomite limestone, gypsum, aluminum fine powder, hollow balloons, alumina, glass powder, aluminum hydroxide, kansuiite, zirconium oxide, antimony trioxide, titanium oxide, molybdenum dioxide, and iron powder.
[0045] The organic compounds include natural polysaccharide powders such as cellulose and chitin, and synthetic resin powders. As the synthetic resin powders, organic powders composed of hard resins, soft rubbers, elastomers, polymers (copolymers), and particles having a multilayer structure such as a core-shell type can be used. Specific examples include acrylic particles, polyamide particles, particles composed of butadiene rubber and / or acrylic rubber, urethane rubber, silicone rubber, polyimide resin powders, fluororesin powders, and phenolic resin powders. These fillers can be used alone or in combination of two or more.
[0046] Examples of the release agent include zinc stearate, calcium stearate, paraffin wax, polyethylene wax, carnauba wax, etc. Preferred are paraffin wax, polyethylene wax, carnauba wax, etc. These release agents can be used alone or in combination of two or more kinds.
[0047] Examples of the thickener include metal oxides and hydroxides such as magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide, and acrylic resin-based fine particles, which can be appropriately selected depending on the handleability of the prepreg of the present invention. These thickeners can be used alone or in combination of two or more kinds.
[0048] The prepreg of the present invention can be obtained by, for example, using a known mixer such as a planetary mixer or a kneader, impregnating the reinforcing fibers (D) with a resin solution prepared by mixing the polyisocyanate (a1), the polyol (a2), and / or (a3), the hydroxyalkyl (meth)acrylate (a4), the ethylenically unsaturated monomer (B), the polymerization initiator (C), and the flame retardant (E), and then sandwiching the resultant from above with a release PET film and rolling it with a rolling machine to obtain a sheet; and, in step 2, allowing the sheet to stand at room temperature to 50°C to react the isocyanate groups of the polyisocyanate (a1) with the hydroxyl groups of the polyol (a2), and / or (a3) and (a4). In step 1, a resin solution in which the polyisocyanate (a1), the polyol (a2), and / or (a3) and (a4) have been partially reacted in advance can also be used, as long as the impregnation into the fiber is not impaired.
[0049] The thickness of the prepreg of the present invention is preferably 0.02 to 1.0 mm. A thickness of 0.02 mm or more is preferable because it is easy to handle for lamination, and a thickness of 1 mm or less is preferable because it is good for resin impregnation. Furthermore, a thickness of 0.05 to 0.5 mm is more preferable.
[0050] As a method for obtaining a molded article from the prepreg obtained above, for example, the release PET film is peeled off from the prepreg, 8 to 30 sheets of the prepreg are laminated, and then the prepreg is placed in a mold preheated to 110°C to 160°C, the mold is closed with a compression molding machine, the prepreg is shaped, and a molding pressure of 0.1 to 10 MPa is maintained to harden the prepreg, and then the molded article is removed to obtain the molded article.
[0051] The molded articles obtained from the prepreg of the present invention are excellent in bending strength, interlaminar shear strength, etc., and therefore can be suitably used for automobile parts, railway vehicle parts, aerospace aircraft parts, ship parts, housing equipment parts, sports parts, light vehicle parts, building and civil engineering parts, housings for office automation equipment, etc. EXAMPLES
[0052] The present invention will now be described in more detail with reference to specific examples. EXAMPLES
[0053] (1) Preparation of resin composition for prepreg A mixture of polymethylene polyphenyl polyisocyanate and diphenylmethane diisocyanate ("Millionate" manufactured by Tosoh Corporation) The mixture consisted of 29.0 parts by mass of 4,4'-diphenylmethane diisocyanate (hereinafter abbreviated as "MDI"), 9.9 parts by mass of hydroxyethyl methacrylate (hereinafter abbreviated as "HEMA"), 26.9 parts by mass of Newpol BPE-20 (manufactured by Sanyo Chemical Industries, Ltd.: EO adduct of bisphenol A, hydroxyl equivalent; 164 g / eq), 6.3 parts by mass of Newpol BPE-40 (manufactured by Sanyo Chemical Industries, Ltd.: EO adduct of bisphenol A, hydroxyl equivalent; 204 g / eq), 0.7 parts by mass of PEG-300 (manufactured by Sanyo Chemical Industries, Ltd.: polyethylene glycol, hydroxyl equivalent; 150 g / eq), 6.3 parts by mass of a thermoplastic resin described below, and MIRAMER as a polymerizable monomer. 12.0 parts by mass of M-245 (Bigen Specialty Chemical Co., Ltd.: bifunctional methacrylate monomer), 1.0 parts by mass of a polymerization initiator (Kayaku Nouryon Co., Ltd.'s "Trigonox 122-C80", organic peroxide), and 30.0 parts by mass of Firecut P-770 (Suzuhiro Chemical Co., Ltd.: ammonium polyphosphate type) as a halogen-free flame retardant were mixed to obtain a prepreg resin composition (1). The ammonium polyphosphate contained in the halogen-free flame retardant is a halogen-free ammonium phosphate salt and contains active hydrogen. The thermoplastic resin was synthesized by mixing 71 parts by mass of PTMG1000 (polytetramethylene ether glycol, manufactured by Mitsubishi Chemical Corporation), 3 parts by mass of 1,4-butanediol (hereinafter abbreviated as "1,4-BG"), and 26 parts by mass of MDI, casting the mixture in a vat, and reacting the mixture at 90°C for 24 hours. The weight average molecular weight of the obtained thermoplastic resin was 50,000.
[0054] (2) Prepreg Preparation The obtained prepreg resin composition was applied to one side of a release PET film, and then carbon fiber ("TRK979PQRW" manufactured by Mitsubishi Chemical Corporation) was impregnated into the film by a hand lay-up method so that the carbon fiber volume content was 55%. The film was then covered with the same release PET film, and aged at 45°C for 24 hours to produce prepreg (1).
[0055] (3) Evaluation of prepregs The obtained prepreg was cut and laminated to obtain a test piece A having a length of 50 mm, a width of 50 mm and a thickness of 2.2 mm. A rapid curing evaluation test was carried out on the obtained test piece A. A thermocouple was sandwiched between two test pieces A and pressed with upper and lower hot plates (press pressure 0.5 MPa). The temperatures of the upper and lower hot plates were 135°C when the polymerization initiator contained in the resin composition for prepreg was Trigonox 122-C80, and 105°C when it was Trigonox 421-70 described below. At this time, the cure time (hereinafter abbreviated as "CT"), which is the time it took for the temperature of the thermocouple to reach the peak top temperature from 30°C, was measured. The air temperature in the test environment was 23±3°C. <Evaluation> ○: CT was within 60 seconds. ×: CT was longer than 60 seconds.
[0056] (4) Evaluation of the molded product The obtained prepregs were laminated to a total thickness of 2 mm. The obtained laminate was filled into the center of a flat plate mold coated with a mold release agent, and compression molded in a compression molding machine under conditions of a pressure of 4 MPa, an upper mold temperature of 140°C, a lower mold temperature of 135°C, and a molding time of 3 minutes, and then cut into a rectangular shape of 125 mm in length and 13 mm in width to produce test piece B as a molded body. A vertical combustion test was conducted in accordance with UL94V. The top end of test piece B was attached vertically to the clamp, and cotton was placed 300 mm below test piece B. A blue flame (20 mm high) of methane gas was applied to the bottom end of test piece B using a gas burner for 10 seconds, and the combustion time was measured. If the combustion lasted less than 30 seconds, the flame was applied for an additional 10 seconds, and the combustion time was measured. Observations were made to see whether the cotton ignited due to the dripping and whether combustion occurred at the clamp attachment position. These procedures were conducted on five test pieces B. The evaluation criteria are shown in Table 1.
[0057] [Table 1] EXAMPLES
[0058] In this example, a resin composition for prepregs was prepared in the same manner as in Example 1, except that Rabitol FP-110 (manufactured by Mitsui Fine Chemicals, Inc.: phosphazene type) was used as the halogen-free flame retardant instead of Firecut P-770. The phosphazene compound contained in the halogen-free flame retardant is a phosphorus compound that does not contain halogen and does not contain active hydrogen. The phosphazene compound does not fall under the category of ammonium phosphate salt. The obtained resin composition for prepreg was used to produce a prepreg in the same manner as in Example 1. A test piece A was produced from the obtained prepreg in the same manner as in Example 1 and evaluated. Furthermore, a test piece B was produced as a molded article from the obtained prepreg in the same manner as in Example 1 and was evaluated. EXAMPLES
[0059] In this example, a resin composition for prepregs was prepared in the same manner as in Example 1, except that 20.0 parts by mass of CR-733S (aromatic condensed phosphate ester, manufactured by Daihachi Chemical Industry Co., Ltd.) was used as the halogen-free flame retardant instead of 30.0 parts by mass of Firecut P-770. The obtained resin composition for prepreg was used to produce a prepreg in the same manner as in Example 1. A test piece A was produced from the obtained prepreg in the same manner as in Example 1 and evaluated. Furthermore, a test piece B was produced as a molded article from the obtained prepreg in the same manner as in Example 1 and was evaluated. EXAMPLES
[0060] In this example, a resin composition for prepregs was prepared in the same manner as in Example 1, except that 2.0 parts by mass of "Trigonox 421-70" (organic peroxide) manufactured by Kayaku Nouryon Co., Ltd. was used instead of 1.0 part by mass of Trigonox 122-C80 as the polymerization initiator. The obtained resin composition for prepreg was used to produce a prepreg in the same manner as in Example 1. A test piece A was produced from the obtained prepreg in the same manner as in Example 1 and evaluated. Furthermore, using the obtained prepreg, a test piece B was produced as a molded body in the same manner as in Example 1, except that the molding conditions were changed to a pressure of 4 MPa, an upper mold temperature of 110°C, a lower mold temperature of 105°C, and a molding time of 8 minutes, and evaluated. EXAMPLES
[0061] In this example, a resin composition for prepregs was prepared in the same manner as in Example 1, except that 2.0 parts by mass of "Trigonox 421-70" (organic peroxide) manufactured by Kayaku Nouryon Co., Ltd. was used instead of 1.0 part by mass of Trigonox 122-C80 as the polymerization initiator. The obtained resin composition for prepreg was used to produce a prepreg in the same manner as in Example 1. A test piece A was produced from the obtained prepreg in the same manner as in Example 1 and evaluated. Furthermore, using the obtained prepreg, a test piece B was produced as a molded body in the same manner as in Example 1, except that the molding conditions were changed to a pressure of 4 MPa, an upper mold temperature of 110°C, a lower mold temperature of 105°C, and a molding time of 8 minutes, and evaluated. EXAMPLES
[0062] In this example, a resin composition for prepregs was prepared in the same manner as in Example 1, except that 2.0 parts by mass of "Trigonox 421-70" (organic peroxide) manufactured by Kayaku Nouryon Co., Ltd. was used instead of 1.0 part by mass of Trigonox 122-C80 as the polymerization initiator, and 20.0 parts by mass of CR-733S (aromatic condensed phosphate ester manufactured by Daihachi Chemical Industry Co., Ltd.) was used instead of 30.0 parts by mass of Firecut P-770 as the halogen-free flame retardant. The obtained resin composition for prepreg was used to produce a prepreg in the same manner as in Example 1. A test piece A was produced from the obtained prepreg in the same manner as in Example 1 and evaluated. Furthermore, using the obtained prepreg, a test piece B was produced as a molded body in the same manner as in Example 1, except that the molding conditions were changed to a pressure of 4 MPa, an upper mold temperature of 110°C, a lower mold temperature of 105°C, and a molding time of 8 minutes, and evaluated.
[0063] [Comparative Example 1] In this comparative example, a prepreg resin composition was prepared in the same manner as in Example 1, except that no flame retardant was added. The obtained resin composition for prepreg was used to produce a prepreg in the same manner as in Example 1. A test piece A was produced from the obtained prepreg in the same manner as in Example 1 and evaluated. Furthermore, a test piece B was produced as a molded article from the obtained prepreg in the same manner as in Example 1 and was evaluated.
[0064] [Comparative Example 2] In this comparative example, a resin composition for prepregs was prepared in the same manner as in Example 1, except that 20.0 parts by mass of MC-6000 (melamine cyanurate type, manufactured by Nissan Chemical Industries, Ltd.) was used as the halogen-free flame retardant instead of 30.0 parts by mass of Firecut P-770. The melamine cyanurate contained in the halogen-free flame retardant is a phosphorus-free compound. A prepreg was produced in the same manner as in Example 1 using the obtained prepreg resin composition. A test piece A was prepared from the obtained prepreg in the same manner as in Example 1 and was evaluated. Furthermore, a test piece B was produced as a molded article from the obtained prepreg in the same manner as in Example 1 and was evaluated.
[0065] [Comparative Example 3] In this comparative example, a resin composition for prepregs was prepared in the same manner as in Example 1, except that 2.0 parts by mass of "Trigonox 421-70" (organic peroxide) manufactured by Kayaku Nouryon Co., Ltd. was used instead of 1.0 part by mass of Trigonox 122-C80 as the polymerization initiator, and that no flame retardant was added. The obtained resin composition for prepreg was used to produce a prepreg in the same manner as in Example 1. A test piece A was produced from the obtained prepreg in the same manner as in Example 1 and evaluated. Furthermore, using the obtained prepreg, a test piece B was produced as a molded body in the same manner as in Example 1, except that the molding conditions were changed to a pressure of 4 MPa, an upper mold temperature of 110°C, a lower mold temperature of 105°C, and a molding time of 8 minutes, and evaluated.
[0066] Tables 2 and 3 below show the formulation of the resin composition for prepreg, the evaluation results of the prepreg, and the evaluation results of the molded article.
[0067] [Table 2]
[0068] [Table 3]
[0069] The prepregs of Examples 1 to 6 contain a halogen-free phosphorus compound as a flame retardant. As shown in Tables 2 and 3, the molded articles produced from the prepregs of Examples 1 to 6 were all UL94 rated as V-0 or V-1. This confirmed that the prepregs of Examples 1 to 6 could be used to produce molded articles with excellent flame retardancy. Furthermore, it was confirmed that the prepregs of Examples 1 to 6 all had a short time to reach the peak top temperature and had excellent fast curing properties.
[0070] On the other hand, the prepregs of Comparative Example 1 and Comparative Example 3 do not contain any flame retardant. The prepreg of Comparative Example 2 contains a compound that does not contain halogen or phosphorus as a flame retardant. As shown in Table 3, the molded articles made from the prepregs of Comparative Examples 1 to 3 did not fall under any of the UL94 evaluations of V-0 to V-2. This confirmed that the prepregs of Comparative Examples 1 to 3 could not produce molded articles with excellent flame retardancy. Furthermore, it was confirmed that the prepreg of Comparative Example 2 took a long time to reach the peak top temperature, and had poor fast curing properties.
Claims
1. The composition comprises a urethane (meth)acrylate (A), an ethylenically unsaturated monomer (B) other than the urethane (meth)acrylate (A), a polymerization initiator (C), a reinforcing fiber (D), and a flame retardant (E), the urethane (meth)acrylate (A) is a reaction product of a polyisocyanate (a1) with a polyol (a2) having an ethylenically unsaturated group and an aromatic skeleton, and / or a reaction product of a polyisocyanate (a1), a polyol (a3) having no ethylenically unsaturated group but an aromatic skeleton, and a hydroxyalkyl (meth)acrylate (a4); The prepreg, wherein the flame retardant (E) comprises one or more halogen-free phosphorus compounds.
2. 2. The prepreg according to claim 1, wherein the halogen-free phosphorus compound is an active hydrogen-free phosphorus compound.
3. 2. The prepreg of claim 1, wherein the halogen-free phosphorus compound is an ammonium phosphate salt.
4. A molded article comprising a cured product of the prepreg according to any one of claims 1 to 3.
Citation Information
Patent Citations
Flame retardant comprising reactive group-containing cyclic phosphazene compound and method for producing the same
JP2008088217A
Photosensitive composition, photosensitive film, photosensitive laminate, method for forming permanent pattern, and printed board
JP2012073589A
Flame-retardant resin composition
JP2012193300A
Prepreg and molded article
WO2021131564A1
Resin composition, prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board
WO2022259851A1
